THE IMPLEMENTATION OF GREEN ACCOUNTING AND ITS IMPLICATION ON FINANCIAL REPORTING QUALITY IN INDONESIA - Enggar Diah Puspa Arum (Journal of Business Studies and Management Review, 2019)
The aim of this study is to analyze whether the implementation of green accounting affecting the financial reporting quality of listed Indonesian manufacturing companies. Earnings sustainability and value relevance are used to represent financial reporting quality from accounting and market aspects. The sample consists of 101 manufacturing companies that listed in Indonesia Stock Exchange determined by using purposive sampling technique and analyzed by using multiple linear regression method. The empirical results indicate that the implementation of green accounting has an effect on earnings sustainability but has no effect on value relevance of accounting information. This study contributes to provide insight how the capital market assesses the implementation of green accounting based on the financial reporting quality. It also expected to improve the company's environmental performance, since it is likely provides implication on the effectiveness of green industry policies.